Discovery of new radio and gamma-ray pulsars associated with unidentified Fermi sources - Bangale, Priyadarshini (My University, 2011)
We report a search for radio pulsation in a sample of 50 faint unidentied gammaray sources not contained in the Fermi Large Area Telescope (LAT) bright source list. Observations were made using the Green Bank Telescope (GBT) operating at 350MHz. We have discovered ten new and three previously detected radio millisecond pulsars in these data. In addition, we have searched for gamma-ray pulsations in Fermi LAT data. We report two new detections of gamma-ray pulsations, one from a new millisecond pulsar discovered in our 50 source Fermi selected survey while the other has been confirmed as a radio pulsar within a separate GBT 350 MHz drift-scan survey. Our new results on gamma-ray selected pulsars will shed light on the nature of Galactic gamma-ray sources, will serve as important probes of fundamental physics such as binary evolution and general relativity, and may be important additions to the pulsar timing array for gravitational wave detection. These new pulsars are among the first of a likely large number of millisecond pulsars associated with unidentified Fermi LAT sources.
Keywords: Astronomi, astrofysik och kosmologi; Grundläggande vetenskaper; Galaktisk astronomi; Astronomy, Astrophysics and Cosmology; Basic Sciences; Galactical astronomy